Pemanfaatan Sistem Informasi Manajemen Desa sebagai Instrumen Pengawasan Badan Permusyawaratan Desa terhadap Kinerja Pemerintah Desa Air Belo Kecamatan Mentok - Jumrin Jumrin; Erwin Erwin; Amri Amri (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study examines the utilization of the Village Management Information Sistem (VMIS) as a supervisory tool employed by the Village Consultative Body (BPD) in overseeing the performance of the village government in Air Belo Village, Mentok District. The research adopted a qualitative approach with a descriptive design. Data were gathered through in-depth interviews, direct observation, and document analysis involving purposively selected informants consisting of BPD members, village officials, and community representatives. Data analysis followed an interactive model encompassing data reduction, data presentation, and conclusion formulation. The results reveal that VMIS has been implemented by the village government primarily to support administrative functions and reporting mechanisms. Nevertheless, its application as an instrument to strengthen BPD’s supervisory role remains suboptimal. BPD supervision is still largely conventional and administrative in nature, with limited reliance on data generated through VMIS. Key obstacles include restricted system access, insufficient technical competence among BPD members, and the absence of internal regulations governing BPD involvement in VMIS utilization. The study concludes that VMIS holds substantial potential to enhance BPD’s supervisory capacity and improve village government performance, provided it is supported by institutional strengthening, human resource capacity development, and a shared commitment to transparent and accountable village governance.